Fibrillar adhesion dynamics govern the timescales of nuclear mechano-response via the vimentin cytoskeleton - Beedle, Amy E. M.; Sharma, Vivek; Oliver-De La Cruz; Jorge; Jaganathan, Anuja; Albajar-Sigalés, Aina; Max, Yavitt F.; Bera, Kaustav; Andreu, Ion; Granero-Moya, Ignasi; Zalvidea, Dobryna; Kechagia, Zanetta; et al. (Springer Nature, 2026)
The cell nucleus is continuously exposed to external signals, of both chemical and mechanical nature. To ensure proper cellular response, cells need to regulate the transmission, timing and duration of these signals. Although such timescale regulation is well described for chemical signals, whether and how it applies to mechanical signals reaching the nucleus is still not fully understood. Here we demonstrate that the formation of fibrillar adhesions locks the nucleus in a mechanically deformed conformation, setting the mechano-response timescale to that of fibrillar adhesion remodelling (~1 h). This process encompasses both mechanical deformation and associated mechanotransduction (such as via YAP), in response to both increased and decreased mechanical stimulation. The underlying mechanism is the anchoring of the vimentin cytoskeleton to fibrillar adhesions and the extracellular matrix through plectin 1f, which maintains nuclear deformation. Our results reveal a mechanism to regulate the timescale of mechanical adaptation, effectively setting a low-pass filter to mechanotransduction.